2011
DOI: 10.1136/bmjopen-2011-000175
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, orbitofrontal structure and function are associated with food choice: a cross-sectional study

Abstract: ObjectivesObesity is on the rise in the US and is linked to the development of type 2 diabetes and cardiovascular disease. Emerging evidence over the last decade suggests that obesity may also adversely affect executive function and brain structure. Although a great deal of research focuses on how diet affects the brain and cognitive performance, no study focuses on how food choice may be associated with brain integrity. Here we investigated how lean and overweight/obese (o/o) adults differed in their food cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
63
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 50 publications
8
63
1
Order By: Relevance
“…For example, administration of a test of cognitive flexibility called the Wisconsin Card Sorting Test revealed increased perseverative errors in 12-year-old obese subjects compared to lean individuals (Cserjesi et al, 2007). Similar results were also observed in adult subjects, where greater perseverative errors were seen in obese adults compared to normal weight controls (Cohen et al, 2011). Further support for these results has been seen in other measures of set shifting; Verdejo-Garcia and colleagues showed that obese individuals had poorer performance during set shifting during an inhibition test and trail making test (Verdejo-Garcia et al, 2010).…”
Section: Obesity and Cognitive Impairmentsupporting
confidence: 74%
See 1 more Smart Citation
“…For example, administration of a test of cognitive flexibility called the Wisconsin Card Sorting Test revealed increased perseverative errors in 12-year-old obese subjects compared to lean individuals (Cserjesi et al, 2007). Similar results were also observed in adult subjects, where greater perseverative errors were seen in obese adults compared to normal weight controls (Cohen et al, 2011). Further support for these results has been seen in other measures of set shifting; Verdejo-Garcia and colleagues showed that obese individuals had poorer performance during set shifting during an inhibition test and trail making test (Verdejo-Garcia et al, 2010).…”
Section: Obesity and Cognitive Impairmentsupporting
confidence: 74%
“…While research has revealed an apparent relationship between obesity and health outcomes like cardiovascular disease and Type 2 diabetes mellitus (T2DM), recent findings have also begun to unveil a relationship between obesity and cognitive decline, as well as various types of neurodegenerative dementias (Sellbom and Gunstad, 2012, Gustafson, 2008, Hassing et al, 2009. Furthermore, while accumulating evidence links obesity to increased risk of Alzheimer's and other types of dementia in later life, the relationship between obesity and cognitive decline has been shown across a range of age groups, from childhood to adulthood (Cohen et al, 2011, Benito-Leon et al, 2013, Reinert et al, 2013.…”
Section: Obesity and Cognitive Impairmentmentioning
confidence: 97%
“…Specifically, research has shown that impulsivity is associated with increased food intake during a laboratory taste test in both healthy weight (Guerrieri, Nederkoorn, & Jansen, 2007) and overweight or obese women (Appelhans et al, 2011). Naturalistic studies have also shown that impulsivity is related to increased body mass index (BMI) (Batterink, et al, 2010;Cohen, et al, 2011), and that highly impulsive people are more likely to be overweight or obese (Guerrieri, et al, 2008;Nederkoorn, et al, 2006;Nederkoorn, et al, 2009;Nederkoorn, Houben, Hofmann, Roefs, & Jansen, 2010;Nederkoorn, et al, 2007;Ryden et al, 2003). Recently, Meule and Platte (2015) found that two forms of impulsivity, namely attentional (an inability to focus attention or concentrate) and motor (acting without thinking), interacted in predicting increased percent body fat in a sample of young women.…”
Section: Introductionmentioning
confidence: 99%
“…A key structure involved in decision-making under uncertainty (i.e., with unknown outcomes) is the orbitofrontal cortex (OFC) [6], a region that shows specific structural and functional variations in overweight/obese as compared to normal-weight children and adults [e.g., [7,8]]. Moreover, a reduced OFC volume has been associated with (un)healthy food choices [9], so a potential association between decision-making deficits and overweight might be mediated by this brain region.…”
Section: Introductionmentioning
confidence: 99%